Phenological Traits Of Soybean In Correlation With Seed Infection By Cercospora Kikuchii (Matsumoto And Tomoyasu) Gardner - D. Ruswandi; R. M. Lantican; R. A. Hautea; M. P. Natural (Zuriat, 2001)
A study was conducted at Institute of Plant Breeding (IPB), University of thePhilippines at Los Ba~nos (UPLB) from February to July 1997 to determine any relationship among various phonological traits with purple seed stain on soybean caused by C. kikuchii. Thirty genotypes that showed different levels of resistance and susceptibility under the 1996 natural field experiment were used in the study. Results suggest that phonological traits in R7-1-R7-2, R7-1-R7-3, R7-1-R8, R7-2-R8 and R7-3-R8 can serve as selection criteria for developing resistance to C. kikuchii.